2021
DOI: 10.1002/psp.2509
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards rural migrants and their influence on return migration in China

Abstract: Compared with the enormous attention paid to the formation of attitudes towards migrants, studies on the social consequences of such attitudes have been insufficient, with the link between attitudes towards migrants and return migration remaining an understudied field both in global and Chinese contexts. Contextual hostility creates social and symbolic barriers in the integration process of migrants and decreases their life satisfaction levels and thus significantly influences many types of migration trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The feeling of being included may lead to a higher level of residential satisfaction, which is a significant trigger for migrants to stay. In addition, the emotional attachment stemming from the feeling of being included could also convince migrants to stay rather than return (Chen & Liu, 2016; Zhou & Tang, 2022). Therefore, compared to the first‐step model that social capital developed from participation in SIE can directly help migrants stay, the second‐ and third‐step models suggest additive explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feeling of being included may lead to a higher level of residential satisfaction, which is a significant trigger for migrants to stay. In addition, the emotional attachment stemming from the feeling of being included could also convince migrants to stay rather than return (Chen & Liu, 2016; Zhou & Tang, 2022). Therefore, compared to the first‐step model that social capital developed from participation in SIE can directly help migrants stay, the second‐ and third‐step models suggest additive explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger attachment to the destination encourage Thai and Mexican migrants' intention to permanently settle in the United States (Korinek et al, 2005; Reyes, 2001). Recent studies on domestic migrants in Chinese cities also found that neighbourhood attachments developed from social bonds contribute to migrants' settlement intention (Mohabir et al, 2017; Sheng et al, 2019; Wu, 2012; Zhou & Tang, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These administrative barriers reduce the willingness of the migrants to settle in the workplace, and tend to keep the group closely tied to the place of emigration. Rural migrants can perceive the attitudes of residents in the place of immigration, which will significantly affect their return decision (Zhou & Tang, 2022). Zhang et al (2020) studied the impact of urban settlement threshold on return migration by using data from 2017 China Household Finance Survey.…”
Section: Economic Factorsmentioning
confidence: 99%
“…Outmigration leads, on the one hand, to the hollowing‐out and decline of the outflow community (e.g., rural villages; Ye, 2018). On the other hand, migration can bring back remittances, economic opportunities, and capital transfers, further elevating the development of the community (Zhou & Tang, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building on that, this study has three different focuses: First and foremost, employing human capital as an analytical concept, it investigates how different human capital accumulation processes, especially migration, affect rural households' productive investment decision‐making. Second, it further investigates the details and mechanisms behind productive investment, exploring the potential reasons why returnees chose to return and why they returned to the traditional agriculture sector rather than the assumed more vivid non‐agricultural sector (Murphy, 1999; Yin et al., 2021; Zhou & Tang, 2021). Third, by examining how return migration can possibly help poverty alleviation, this research provides a reference for other more general developing areas, offering a perspective on how to break through the limitations of regional poverty and advance corresponding policy suggestions.…”
Section: Introductionmentioning
confidence: 99%